The garbhagriha and the maha mandapa with concrete domes - Temples of India Project Team (Jio Institute, 2024)
Debris from the original temple was reassembled to form the adhisthana, the maha mandapa and the garbhagriha. These have been assembled in parts to form the jagati (raised platform). However, it is not known where they were located in the original temple. The space in front of the garbhagriha (sanctum sanctorum) is the maha mandapa which is used as a congregation space and for conducting rituals. Instead of the traditional shikhara over the garbhagriha, the temple was reconstructed with concrete domes over the garbhagriha and the maha mandapa.